Symmetric Multiple Carbohelicenes - Kato, Kenta; Segawa, Yasutomo; Itami, Kenichiro (Synlett, 2019)
This account focuses on the synthesis and structures of symmetric multiple carbohelicenes; i.e., fully fused polycyclic aromatic hydrocarbons containing two or more symmetric helicene moieties. Synergies of the multiplexed helicene structures within a π-system generate a number of local minima and transition states between each state. Based on recent studies on multiple helicenes, a systematic molecular design for further multiplexed symmetric helicenes is proposed in the last section of this article.
Keywords: nonplanar π-systems; polycyclic aromatic hydrocarbons; helicene; multiple helicene